Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fphys.2019.01366
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Changes of Healthy Lowlanders at Different Altitude Levels: A Systematic Review and Meta-Analysis

Abstract: Background: High altitude, characterized by hypobaric hypoxia, low temperature, and intensive ultraviolet radiation, is identifiably one of the examples of scientific enquiry into aviation and space analogs. However, little is known about the ocular physiological response, especially intraocular pressure (IOP) changes at high altitude.Objectives: This study aimed to systematically review of high altitude exposure on IOP for healthy lowlanders with unoperated eyes.Methods: A comprehensive systematic literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
(27 reference statements)
0
10
1
Order By: Relevance
“…In a previous study, Bruttini et al [7,8] found a statistically signi cant decrease in mean IOP at 3466 m compared to sea level in the moderate altitude range of 1300 m (19°C) to 3466 m (-1.4°C), which is inconsistent with our observations. We speculate that this may be due to a signi cant decrease in temperature at 3466 m resulting in IOP changes.…”
Section: Discussioncontrasting
confidence: 99%
“…In a previous study, Bruttini et al [7,8] found a statistically signi cant decrease in mean IOP at 3466 m compared to sea level in the moderate altitude range of 1300 m (19°C) to 3466 m (-1.4°C), which is inconsistent with our observations. We speculate that this may be due to a signi cant decrease in temperature at 3466 m resulting in IOP changes.…”
Section: Discussioncontrasting
confidence: 99%
“…A few (10%) of the cold receptors were silenced when the temperature increased, and the firing rate of the cold receptors was increased when the surface temperature of the cornea decreased (Patel et al 2021 ). So sudden physiological responses are consistent with the steep increase in risk that was associated with extreme temperature events (Mansouri et al 2022 , Yang et al 2019b ).…”
Section: Discussionmentioning
confidence: 69%
“…Overall, the studies relating altitude and IOP were mixed; therefore, it was necessary to summarize the relevant results. Yang et al (2019) conducted a meta-analysis on IOP changes at different altitudes. The data showed that IOP significantly decreased with the increase in altitude between 3,000 and 5,500 m, whereas IOP increased at extreme altitudes of over 5,000 m. They also found that a duration of exposure of more than 72 h was likely to induce a decrease in IOP.…”
Section: Influences On Visual Functionmentioning
confidence: 99%
“…The high-altitude hypobaric hypoxia environment clearly effects intraocular pressure (IOP) (Albis-Donado et al, 2018;Najmanova et al, 2018). Yang et al (2019) and Bruttini et al (2020) illustrated that within the moderate altitude range of 1,300 m (19°C) to 3,466 m (−1.4°C), the average IOP at 3,466 m was statistically lower than that at sea level, and altitude significantly correlated with IOP. Subsequently, Willmann et al ( 2017) studied IOP at 4,559 m after 3 days and found no significant change compared with baseline levels.…”
Section: Influence On Intraocular Pressurementioning
confidence: 99%